Strand 2: Bringing competence areas together: A collaborative approach to delivering and receiving networked learning - Sletvold, Mary (Proceedings of the International Conference on Networked Learning, 1998)
Do ODL - Dissemination of Open and Distance Learning, is a project granted within the European Commission programme SOCRATES, where important issues for dissemination of ODL in higher education arc addressed. One objective of Do ODL is to define models for collaboration between European academic institutions in order for them to function as centres for each other in the field of ODL. As a part of the field trials in Do ODL, a course in "Strategic Internet Marketing" have been developed as a joint effort by the participating institutions. The group developing the course consists of lecturers within different fields in marketing and computer engineering, and with various experience in producing and delivering networked learning courses. Collaborative learning is being used as an integrated part of the course delivery, with a possibility for the students to choose between face to face collaboration and networked depending on what is most appropriate for each student. The result of this interdisciplinary, inter-institutional and international approach is, as far as the lecturers and the institutions are concerned, collaborative course development and delivery. With respect to the students, they are offered an active learning situation based upon a collaborative learning environment. The course will be run for the fuse time during the spring term of 1998. The experiences regarding the course delivery will not be clear until after the course have been accomplished in June. This paper will focus on the development and implementation process and the experiences gained during this activities. However, activities related to the planning process of the course concerning delivery and accomplishment of the course, will be covered.